Optimal conductor size selection and reconductoring in radial distribution systems using a mixed-integer LP approach - Franco, John F. [UNESP]; Rider, Marcos J. [UNESP]; Lavorato, Marina [UNESP]; Romero, Rubén [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This paper presents a mixed-integer linear programming model to solve the conductor size selection and reconductoring problem in radial distribution systems. In the proposed model, the steady-state operation of the radial distribution system is modeled through linear expressions. The use of a mixed-integer linear model guarantees convergence to optimality using existing optimization software. The proposed model and a heuristic are used to obtain the Pareto front of the conductor size selection and reconductoring problem considering two different objective functions. The results of one test system and two real distribution systems are presented in order to show the accuracy as well as the efficiency of the proposed solution technique. © 1969-2012 IEEE.
Keywords: Distribution system optimization; Mixed-integer linear programming; Optimal conductor size selection; Distribution systems; Linear expression; Mixed integer linear programming; Mixed-integer; Objective functions; Optimality; Optimization software; Pareto front; Radial distribution systems; Re-conductoring; Real distribution; Size selection; Solution techniques; Steady-state operation; Test systems; Integer programming; Local area networks; Optimization